(untitled) (Lapai Journal of Economics, 2024)
The yearly budgetary allocation on subsidy in Nigeria has remained a concern for policymakers and other agents of the economy as to whether it has achieved the targeted goal of economic growth in Nigeria. Thus, this study examined the impact fuel subsidy payments had on economic growth in Nigeria from 2005 to 2023. Secondary data were sourced from the Central Bank of Nigeria (CBN) Statistical Bullentin, the World Bank World Development Indicator (WDI) and the Nigerian Extractive Industry Transparency Initiative (NEITI) working paper. The data were converted into quarterly data for ease of analysis and estimation. Gross Domestic Product (GDP) growth rate was used as the dependent variable while Fuel Subsidy Expenditure (FSE), Exchange Rate (EXC) and Inflation Rate (INF) were the independent variables. The long run relationship among the variables was confirmed using the Johansen Co-integration technique while the Vector Error Correction Model (VECM) technique of analysis was adopted for estimation of the data. The study found that a negative significant relationship exists between fuel subsidy expenditure and economic growth in Nigeria within the period under study. The study therefore recommends a re-direction of government expenditure on subsidy to other critical area of the economy that can propel the growth of the economy.